Development of a New Process for Tulobuterol Hydrochloride - Chuan-Jun Wu; Peng Peng; Lin-Tao Xia; Xu Liu; Cai-Xia Yu; Zhi-Bo Zheng; Chuan-Meng Zhao; Fu-Li Zhang (Georg Thieme Verlag KG, 2023)
Tulobuterol is a selective β2-adrenoceptor agonist and has been widely utilized as a therapeutic agent for the treatment of asthma. Synthesis of tulobuterol has achieved many important progresses over the past decades and has gradually become one of the research hotspots in organic chemistry. This study aimed to explore a novel synthesis route to synthesize tulobuterol hydrochloride (1), an active ingredient of Chlobamolie Hydrochloride Tablets. In the study, 1 was obtained from the cost-effective, commercially available 2-chloroacetophenone through the key steps including the reactions of bromination, NaBH4 reduction, and amination. Process-related impurities were also investigated. 1 was obtained with excellent purity (99.96%) in 53% overall yield without the need for chromatographic purification. The developed method is green, facile, and cost-effective; thus, it is suitable for the industrial-scale production of 1.